2017
DOI: 10.1039/c7tb00800g
|View full text |Cite
|
Sign up to set email alerts
|

C60@lysozyme: a new photosensitizing agent for photodynamic therapy

Abstract: C60@lysozyme showed significant visible light-induced singlet oxygen generation in a physiological environment, indicating the potential of this hybrid as an agent for photodynamic therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(44 citation statements)
references
References 85 publications
2
42
0
Order By: Relevance
“…[81,82] The lysozyme·C 60 complexp roduced 1 O 2 following visible-light irradiation and showedp hotoinduced cytotoxicity toward HeLa cells. [83] As discussed in Section 2.4, LMIC 60 preparedb yu sing the exchange methodh ad highers olubility ands tability than that prepared by using the premixing method.L MIC 60 prepared throught he two methods had different photoinduced cytotoxicities toward HeLa cells. Cell viability was determined by using aW ST-8 assay (Cell Counting Kit-8: Dojindo Laboratories Co., Kumamoto, Japan).…”
Section: Photoinduced Cytotoxicities Of C 60mentioning
confidence: 98%
See 1 more Smart Citation
“…[81,82] The lysozyme·C 60 complexp roduced 1 O 2 following visible-light irradiation and showedp hotoinduced cytotoxicity toward HeLa cells. [83] As discussed in Section 2.4, LMIC 60 preparedb yu sing the exchange methodh ad highers olubility ands tability than that prepared by using the premixing method.L MIC 60 prepared throught he two methods had different photoinduced cytotoxicities toward HeLa cells. Cell viability was determined by using aW ST-8 assay (Cell Counting Kit-8: Dojindo Laboratories Co., Kumamoto, Japan).…”
Section: Photoinduced Cytotoxicities Of C 60mentioning
confidence: 98%
“…reported that lysozyme was able to disperse even pristine C 60 monomolecularly in water with a 1:1 stoichiometry . The lysozyme ⋅ C 60 complex produced 1 O 2 following visible‐light irradiation and showed photoinduced cytotoxicity toward HeLa cells …”
Section: Photoinduced Cytotoxicity Of Fullerenes Incorporated Into Somentioning
confidence: 99%
“…Since fullerenes are ideal electron mediators, C 60 @protein hybrids can lead to new applications of C 60 in electrochemical catalytic systems or in biosensing. [10][11][12] Photoinduced reactive oxygen species (ROS) generation by C 60 @lysozyme hybrids C 60 shows a significant visible light-induced generation of ROS, that can be exploited in photodynamic therapy [76][77][78][79][80][81][82][83][84][85][86][87] or photocatalysis. [88][89][90][91] However, the use of C 60 molecules in water still presents important restrictions in its application due to both the dependency of C 60 properties on the physiological environment and the related aggregation phenomena 92 and C 60 poor solubility.…”
Section: Electrochemical Characterization Of C 60 @Lysozyme Hybridsmentioning
confidence: 99%
“…The high performances of C 60 @lysozyme in the visible light-induced generation of ROS in water suggest the potential use of this hybrid as an agent for photodynamic therapy. [76][77][78][79][80][81][82][83][84][85][86][87] Photogenerated singlet oxygen can be used also in synthetic organic chemistry. Even though singlet oxygen is a short-lived metastable excited state of molecular oxygen, it is a practical reagent for compound oxidation and can form carbon-oxygen and heteroatom-oxygen bonds.…”
Section: Electrochemical Characterization Of C 60 @Lysozyme Hybridsmentioning
confidence: 99%
“…The hybrid is well-defined and the fullerene binds selectively in the protein-substrate binding pocket. The protein-based supramolecular adduct preserves the photophysical properties of C60 and allows the exploitation of C60 as a photosensitizer for photodynamic treatments [34].…”
Section: Introductionmentioning
confidence: 99%